Fabrication and Characterization of Polyvinyl Alcohol-Chitosan Mixed Matrix Membrane - Zainul Zariff Zainul Hisham,; Muhammad Ihsan Zulkifli,; Aqil Naufal Mahdani,; Mohd Adnan, Raudah; Basirah Fauzi, (Multidisciplinary Applied Research and Innovation, 2026)
Polyvinyl alcohol (PVA) and chitosan (CS) are biodegradable polymers with promising potential in membrane fabrication. However, a notable gap remains in identifying the optimal PVA-CS composition and additive concentrations that enhance membrane performance. This study seeks to address that gap by building on previous research to advance membrane technology for water treatment applications. In this study, blend membranes were prepared by mixing 1 wt% chitosan (dissolved in 2% v/v acetic acid) with varying concentrations of PVA (6 wt%, 8 wt%, 10 wt%, 12 wt%, and 14 wt%), using 5 wt% sorbitol as a plasticizer. The PVA and CS solutions were mixed in a 1:1 volume ratio and cast using the solution casting method. The membranes were characterized using swelling analysis, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and tensile strength testing. FTIR results showed a decrease in O–H peak intensity with increasing PVA content, indicating stronger hydrogen bonding between PVA and CS. SEM images revealed smoother and more uniform surfaces at higher PVA concentrations. Swelling tests demonstrated that water uptake decreased with increasing PVA content. Specifically, at 6 g PVA, the swelling index was 4.8056%, whereas at 8 g PVA, it dropped to 3.7548%. Tensile strength analysis showed that increasing the PVA content from 6 g to 8 g significantly enhanced the mechanical properties, with the Young’s Modulus rising from 7642.58 MPa to 13438.71 MPa. Overall, the results demonstrate that increasing PVA concentration enhances the membrane’s structural and mechanical integrity, suggesting potential for water-related separation applications.